The Actualization of Woman Empowerment in Islamic Economy - Sumarin, Sumarin (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
Islam really appreciates the dignity, the prestige, and the woman"™s right, without the different to the man. The mowan"™s moval in today context is the moval which has value, meaning and the potential itself. The woman empowerment program to the woven fabric craftsman which have been done in Sumber Harapan village, Sambas regency is the real woman self-actualization in Indonesia. The research is a field research. The technique of data collecting is observation, interview and documentation. The analysis technique in this research is  analysis model interactive and SWOT analysis. According to the data analysis and explanations that the strategy of woman empowerment reinforcement to the woven fabric craftsman in Sumber Harapan village, Sambas regency include: 1). Increase the product intensification and diversification.          2). The utilization   of work ethic to expanding the access of market. 3) the integrated founding and development to increase the quality of human resources. 4). Utilize the government supports and the private to consolidate the financing in increasing the means and the infrastructure. 5) Increase the cooperation with the competent institution .